Penggunaan model pembelajaran problem based learning (PBL) berbantuan youtube untuk meningkatkan keterampilan berbicara peserta didik kelas v di sekolah dasar - Karisma, Mia; Chumdari, Chumdari (Didaktika Dwija Indria, 2026)
This research aims to improve the speaking skills of fifth grade students at Langenharjo 01 Sukoharjo Elementary School through the implementation of the Problem Based Learning (PBL) model supported by YouTube media. This research is categorized as Classroom Action Research (CAR), designed to take place over two cycles. Each cycle involves four key steps: planning, implementation of actions, observation, and reflection. The subjects is 17 students. Data collection was observation, interviews, documentation, and tests, then analyzed descriptively qualitatively and quantitatively. The results of the study showed an increase in the speaking skills of students after using the Problem Based Learning (PBL) model with the help of YouTube. The evidence is that the students' learning completeness increased from 12% in the pre-action phase, to 44% in Cycle I, and finally reaching 83% in Cycle II. The average score of the students also improved, from 63 (pre-action), to 72 (Cycle I), and 82 (Cycle II). This, it can be concluded the implementation PBL model supported by YouTube media is effective in improving the speaking skills of fifth-grade students at SD Negeri Langenharjo 01 Sukoharjo.